FROM THEORY TO PRACTICE: REFLECTIVE EXPERIENCE OF RURAL PRE-SERVICE ENGLISH TEACHERS DURING TEACHING PRACTICUM IN AN INDONESIAN ISLAMIC HIGHER EDUCATION CONTEXT - Ayu Meiratnasari; Ema Wilianti Dewi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
The teaching practicum is a critical component of preparing pre-service teachers, bridging theoretical knowledge and authentic classroom experiences. Despite its importance, there is limited research on how rural pre-service English teachers reflect on their practicum experiences within Islamic educational contexts. This study investigated (1) the reflective processes of rural pre-service English teachers during their teaching practicum, (2) the challenges they faced, and (3) the practicum’s contribution to their professional development and teacher identity formation. Utilizing a qualitative exploratory design, the study engaged three pre-service English teachers from an Islamic Higher Education Institution in South Sumatra, Indonesia. Data were collected through written reflective reports and analyzed using Reflexive Thematic Analysis. Four interconnected themes emerged: the development of professional teacher identity through experiential learning, the navigation of student diversity via adaptive teaching practices, the acquisition of ethical and relational teaching dimensions, and the adoption of a holistic teaching mission in Islamic schools. The findings indicate that the teaching practicum functioned as a transformative learning experience, enhancing participants’ self-confidence, pedagogical awareness, reflective capacity, and professional competence. Major challenges included student diversity, low English proficiency, limited motivation, and restricted instructional time. Participants demonstrated adaptability by modifying instructional strategies and contextualizing learning materials to address learners’ needs. The study also found that the Islamic school context contributed to the development of a holistic teacher identity, encouraging participants to view themselves as language instructors, character educators, moral role models, and facilitators of students’ spiritual development. These findings underscore the significance of reflective practicum experiences in fostering adaptive, ethical, and holistic teacher development in rural educational settings.